The incidence and influencing factors of postoperative acute kidney injury in elderly patients with hip fractures: A meta-analyses. - Chong Hou; Peizhe Zhang; Yuan Xue; Jinli Guo (PLoS ONE)
Objective Acute kidney injury (AKI) is one of the common complications after hip fracture in the elderly, and its hospitalization rate, mortality rate and medical expenses are high, resulting in serious social and economic burden. Therefore, we aim to systematically evaluate the incidence and risk factors of postoperative AKI in elderly patients with hip fracture, so as to identify the occurrence of postoperative AKI in elderly patients with hip fracture early, so as to prevent it in advance. Methods This meta-analysis adhered to PRISMA guidelines and was registered in PROSPERO (CRD42024498009).We systematically searched Embase, Pubmed, web of science, the cochrane Library, CBM, VIP, CNKI, and Wanfang Data to collect studies on the incidence or influencing factors of postoperative acute kidney injury in elderly patients with hip fracture published up to 18 December 2023. All studies were screened, relevant data extracted, and quality assessed by two independent authors, and meta-analysis was performed using Stata 15.0 software. Results A total of 22 articles were included, with a total sample size of 25195 cases and 16 influencing factors. The results of meta-analysis showed that the incidence of postoperative AKI in elderly patients with hip fracture was 17.2% [95%CI (14.3% ~ 20%), P < 0.0001], and there were 6 statistically significant influencing factors, which were baseline serum potassium [OR(95%CI)=2.23 (1.22, 4.05)], hypertension [OR(95%CI)=3.00 (1.75, 5.88)], and chronic kidney disease [OR(95%CI)=4.40 (1.10, 14.75)], diabetes mellitus [OR (95% CI) = 1.84 (1.19, 2.83)], intraoperative hypotension [OR (95% CI) = 5.61 (3.36, 9.35)], and operative time [OR (95% CI) = 1.01 (1.00, 1.02)]. Conclusions Our study indicated that the incidence of postoperative AKI in elderly patients with hip fracture was 17.2%. Baseline serum potassium, hypertension, chronic kidney disease, diabetes, operative hypotension and operation time were the influencing factors of postoperative AKI in elderly patients with hip fracture. PROSPERO registration number for this study: CRD42024498009.